Small Rodent Fluctuations in Arid Ecosystems: Natural Laboratories for Testing Population Dynamic Theory - Lima, Mauricio (Annals of Arid Zone, 2016)
The dramatic responses of primary productivity to rainfall variability in deserts represent a unique opportunity for testing basic principles of population dynamic theory. In particular, these ecosystems are natural laboratories for studying the relative importance of the feedback structure (intrinsic processes) and exogenous (climatic or environmental) factors in determining population dynamics, in particular because the interaction between density-dependence and climate is a major question in population ecology. In this article, I review the findings from two different deserts about the role of rainfall in determining population dynamics of small rodents. Previous studies using long-term data from small rodent monitoring in northern Chile and southwestern USA have applied simple theoretically based population dynamics models for understanding small rodent fluctuations. The findings show that simple models can be useful in explaining and predicting the dynamics of natural populations, particularly when they are based on a sound theoretical framework. In particular, Royama’s classification of exogenous perturbation effects has been extremely useful in population modeling. Using these 1)10dels together with Royama’s paradigm for classifying exogenous (climate) perturbations, it is possible to distinguish how rainfall influences the limiting factors (food) in small rodent populations. The remarkable simplicity and generality of the models used appear to be very successful in explaining rodent fluctuations at different arid ecosystems such as southwestern North America and western South America, suggesting that this is a strong and useful approach for incorporating the role of exogenous factors such as climate into population models. Key words: Desert rodents, intra-specific competition, limiting factors, rainfall, theoretical models.